Pengaruh Economic Value Added (Eva) Dan Market Value Added (Mva) Terhadap Return Saham - Luke Suciyati Amna (Jurnal Akuntansi dan Keuangan, 2020)
This study aims to empirically examine the effect of Economic Value Added and Market Value Added on stock returns on property and real estate companies listed on the Indonesian stock exchange, the period used in this study is from 2015-2017. This research uses quantitative methods. The sampling technique in this study used a purposive sampling technique.based on prederemined criteria obtained a sampel of 15 companies for 3 years with 45 observation lists.the data analysis technique used is multiple liniear regression. Based on these results it shows that: Economic Value Added (EVA) has a positive and significant effect on stock returns and Market Value Added (MVA) has a positive and significant effect on stock return.